Effect of Supplementation of Probiotics on the Performance of Vanaraja Chicks - Swain, B.K.; Naik, P.K.; Chakurkar, E.B.; Singh, N.P. (Indian Journal of Animal Nutrition, 2018)
A study was conducted to assess the effect of supplementation of Prosol (a probiotics preparation) in drinking water on the performance of Vanaraja chicks. Vanaraja chicks (N=72, 3 weeks old) were randomly distributed into 4 equal groups (replicated into 3 groups of 6 chicks each). The chicks were reared on wire mesh floored cages and offered standard chick ration (T1), standard chick ration + Prosol @ 0.1 g/L of drinking water (T2), standard chick ration + Prosol @ 0.2 g/L of drinking water (T3) and standard chick ration + Prosol @ 0.3 g/ L of drinking water (T4). The results indicated that body weight gain was higher (P<0.5) in chicks with supplementation of Prosol @ 0.2 g/L of drinking water at 13 weeks of age. Feed intake was not affected by the supplementation of probiotics through drinking water. The feed conversion ratio improved significantly (P<0.5) and cost benefit analysis indicated that the net profit was higher in chicks given Prosol through drinking water @ 0.2 g/L. It was concluded that supplementation of probiotics (Prosol) @ 0.2 g/L of drinking water was beneficial in terms of higher body weight gain and better feed conversion ratio in growing Vanaraja chicks.